Educating Social Workers in Palliative and End-of-Life Care: Development and Implementation of a New National Training Program - Glajchen, Myra; Otis-Green, Shirley; Berkman, Cathy; Portenoy, Russell K (Journal of palliative medicine, 2024)
Educating Social Workers in Palliative and End-of-Life Care (ESPEC) is a nationally scalable continuing education program designed to improve the knowledge and skills of frontline health social workers caring for patients with serious illness. This article describes ESPEC's rationale, development, and initial implementation. Following the creation of consensus-derived core primary palliative care competencies for health primary care social workers based on the eight domains of palliative care outlined in the National Consensus Project Guidelines for Quality Palliative Care, an evidence-based curriculum was developed. This was used to develop a hybrid training model with a self-study component, synchronous instructor-led skills-based training, leadership training, and mentorship. The interactive curriculum incorporates patient scenarios highlighting the health social work role. Training targets high-impact skills-the biopsychosocial-spiritual assessment, advance care planning, family meetings, and interprofessional communication-and professional development. ESPEC was launched in the United States in collaboration with the National Association of Social Workers (NASW) and the Social Work Hospice and Palliative Care Network (SWHPN). The preliminary launch demonstrated high user acceptability, positive ratings for content and format, and gains in knowledge and competence. Data suggest that ESPEC can increase health social workers' knowledge and confidence as providers of palliative care interventions. National dissemination is ongoing.